2021
DOI: 10.1002/ecs2.3733
|View full text |Cite
|
Sign up to set email alerts
|

Testing the strength and direction of selection on vocal frequency using metabolic scaling theory

Abstract: A major challenge for studies assessing drivers of phenotypic divergence is the statistical comparison of taxa with unique, often unknown, evolutionary histories, and for which there are no clear expected trait values. Because many traits are fundamentally constrained by energy availability, we suggest that trait values predicted by scaling theories such as the metabolic theory of ecology (MTE) can provide baseline expectations. Here, we introduce a metabolic scaling-based approach to test theory involving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…As a proxy for agents of selection that vary with latitude, we used the absolute value of either the minimum or maximum latitude, whichever was larger. This measure has the advantage that it cannot result in an uninhabited location, which can occur with species with discontinuous ranges when a midpoint is used [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a proxy for agents of selection that vary with latitude, we used the absolute value of either the minimum or maximum latitude, whichever was larger. This measure has the advantage that it cannot result in an uninhabited location, which can occur with species with discontinuous ranges when a midpoint is used [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although it is unclear whether sources of noise in these studies elevated sounds above ambient conditions at a scale relevant to breeding birds, unchanged distributions with respect to noise exposure could be explained by habitat filtering by vocal frequency. Several studies suggest that birds that inhabit grasslands and other open environments have higher-frequency vocalizations than would be expected on the basis of allometric scaling alone (Francis & Wilkins 2021) or in comparison to birds in more densely vegetated environments (Weir et al 2012; but see Mikula et al 2021). Whether this vocal trait could explain the absence of responses among grassland birds is an open question; however, highfrequency singing as a preadaptation to areas characterized by noise has support elsewhere.…”
Section: Noise Filtering By Traitsmentioning
confidence: 99%
“…Avoidance of noise (gray) by Woodhouse's scrub jays (blue) increases nest success in songbirds (brown) via lower rates of nest predation by jays (Francis et al 2009) and increases densities of black-chinned hummingbirds (purple), which strongly avoid jays when nesting (Greeney et al 2015). Elevated densities of hummingbirds increase pollination of hummingbird-pollinated plants (red) (Francis et al 2012), yet the avoidance of noise by jays negatively affects recruitment of piñon pine (green) (Francis et al 2021), a woodland foundational species that receives seed dispersal services from jays.…”
Section: Indirect Responses To Noisementioning
confidence: 99%
“…Recent studies on song frequency across over 5000 passerine species found that although there is evidence supporting a relationship between song frequency and body mass, there is no generalized relationship between song frequency and habitat (Mikula et al 2020). These results suggest that variation in passerine song frequency may be primarily driven by selection for morphology, rather than habitat-related selection on sound (Mikula et al 2020, Francis andWilkins 2021); however, recent evidence supports sensory drive within species (Sebastianelli et al 2022). Part of the reason for the mixed results of sensory drive is that previous studies are unclear on what portion of the hypothesis they are testing (Cummings and Endler 2018).…”
Section: Introductionmentioning
confidence: 97%